KAJIAN SOSIOLOGI EKONOMI DALAM TRANSAKSI JUAL BELI SAWIT DI JORONG PASIR PANJANG, KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Annisa, Winda; Marleni, Marleni; Rahmadani, Sri (Universitas Tanjungpura, 2022)
This research is motivated by the obstacles experienced by oil palm farmers in buying and selling palm oil transactions, making palm oil tokens have the opportunity to maintain relationships between them by making loans known as the stock planting system. The purpose of this study was to describe the stock planting system between oil palm farmers and toke palm oil. The theory used is the patron-client theory proposed by James C. Scott. This research approach is a qualitative approach with a descriptive type. The types of data in this research are primary and secondary data. There were 10 informants in this study. Data collection methods used are observation, in-depth interviews and document studies. The result of this research is the buying and selling transactions carried out are transactions between toke and farmers. In meeting the necessities of life, farmers make loans to toke called stock planting. In this stock planting system, oil palm farmers are required to sell their crops to the token, they must be loyal to selling to the token, they are not allowed to sell to other tokens. If this happens, then the oil palm farmers are obliged to pay or return the money that has been taken, the oil palm farmers are allowed to pay in installments or not and the oil palm farmers are also allowed to determine how many installments they want to be given.